2008
DOI: 10.1002/cmdc.200700223
|View full text |Cite
|
Sign up to set email alerts
|

Hyrtiosal, from the Marine Sponge Hyrtios erectus, Inhibits HIV‐1 Integrase Binding to Viral DNA by a New Inhibitor Binding Site

Abstract: HIV-1 integrase (IN) is composed of three domains, the N-terminal domain (NTD, residues 1-50), the catalytic core domain (CCD, residues 51-212), and the C-terminal domain (CTD, residues 213-288). All the three domains are required for the two known integration reactions. CCD contains the catalytic triad and is believed to bind viral DNA specifically, and CTD binds viral DNA in a nonspecific manner. As no clear evidence has confirmed the involvement of NTD in DNA binding directly, NTD has not been seriously con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Further research showed that 233 displayed potent activity for abolishing the retardation of AKT membrane translocation caused by PTP1B overexpression in CHO cells, dramatically enhanced the membrane translocation of the key glucose transporter Glut4 in PTP1B-overexpressed CHO cells, and effectively facilitated insulin inhibition of Smad2 activation. Moreover, hyrtiosal 233 was found to inhibit HIV-1 integrase from binding to viral DNA by a new inhibitor binding site [153] .…”
Section: Sesterterpenesmentioning
confidence: 99%
“…Further research showed that 233 displayed potent activity for abolishing the retardation of AKT membrane translocation caused by PTP1B overexpression in CHO cells, dramatically enhanced the membrane translocation of the key glucose transporter Glut4 in PTP1B-overexpressed CHO cells, and effectively facilitated insulin inhibition of Smad2 activation. Moreover, hyrtiosal 233 was found to inhibit HIV-1 integrase from binding to viral DNA by a new inhibitor binding site [153] .…”
Section: Sesterterpenesmentioning
confidence: 99%
“…The N-terminal domain (NTD) of IN (residues 1-50) contains a zinc finger motif, HHCC, that mediates viral DNA binding and is essential for viral replication (19 -23). A natural product, hyrtiosal, has been shown to inhibit IN through direct binding to the NTD of IN (24). Such a targeting of the NTD of IN could disrupt Zn 2ϩ coordination by the zinc finger motif and have a detrimental effect on viral DNA binding, IN multimerization, and reverse transcription and/or integration.…”
mentioning
confidence: 99%
“…In brief, Escherichia coli BL21(DE3) cells transformed with wild-type or mutated HIV-1 IN expression plasmids were grown at 37 °C in Lysogeny Broth (LB) medium containing 100 µg/mL ampicillin until the optical density at 600 nm reached 0.6−0. Competitive inhibition assay The compound's competitive inhibition assay against IN/viral DNA binding was performed by using the surface plasma resonance (SPR) biosensor technology-based Biacore 3000 system (Biacore AB, Uppsala, Sweden) as previously reported [19] . During the assay, a 21 bp 5´-biotinylated oligonucleotide (5´-GTGTGGAAAATCTCTAGGTGT-3´) hybridized with a non-biotinylated complementary oligonucleotide was immobilized on the streptavidin matrix-coated sensor chip (SA chip), and 200 nmol/L IN incubated with 0-0.2 mmol/L compounds for 1 h at 4 °C flowed over the chip surface.…”
Section: Methodsmentioning
confidence: 99%